Face perception and processing in early infancy: inborn predispositions and developmental changes - Simion, Francesca; Giorgio, Elisa Di (Frontiers in Psychology, 2015)
From birth it is critical for our survival to identify social agents and conspecifics. Among others stimuli, faces provide the required information. The present paper will review the mechanisms subserving face detection and face recognition, respectively, over development. In addition, the emergence of the functional and neural specialization for face processing as an experience-dependent process will be documented. Overall, the present work highlights the importance of both inborn predispositions and the exposure to certain experiences, shortly after birth, to drive the system to become functionally specialized to process faces in the first months of life.